PERSEPSI GURU TENTANG GAYA PENGELOLAAN KONFLIK OLEH KEPALA SEKOLAH DI SEKOLAH MENENGAH PERTAMA NEGERI SE-KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Yogie Afdhal (Universitas Negeri Padang, 2014)
The goal of this research are to describe teacher’s perception about management conflict style the headmasters junior high school in the Kampung Dalam Subdistrict Padang Pariaman Residence. We can see the style about avoid style, compromise, competition, accommodations, and collaboration. The population are 102 with sampel 55 persons take by formulation Cochran. Instrumental of this research is cuesioner form of Likert scale which has test validity and reliability. Key word : Management Conflict Style